Snacking Behaviour and Its Determinants among College-Going Students in Coastal South India - Prasanna Mithra; Bhaskaran Unnikrishnan; Rekha Thapar; Nithin Kumar; Sharana Hegde; Anjali Mangaldas Kamat; Vaman Kulkarni; Ramesh Holla; B. B. Darshan; Kanchan Tanuj; Vasudev Guddattu; Avinash Kumar (Journal of Nutrition and Metabolism)
Background. Consumption of snacks in between the regular meals is a poor snacking behaviour. It is an established risk factor for several lifestyle-related disorders and has long-term effects among the younger individuals. Objectives. To study the snacking behaviour and to assess their determinants among college-going students. Methods. This cross-sectional study was conducted among 865 college-going students in Mangaluru. Data were collected using a pretested pro forma that was coded and analyzed using Statistical Package for Social Sciences (SPSS) version 11.5. The chi-square test and random-effect logistic regression analyses were used. Results. Overall, there were 52.4% females and 47.6% males, and 76.8% of them were aged <20 years. More than half of the participants (54.3%) had the habit of snacking in between regular meals. Among them, a large proportion (78.7%) did not have any specific timings for snacking. Also, 51.1% of the students were snacking while watching TV, and 31.9% of them snacked while studying. Breakfast was the most commonly skipped meal (26.2%); of those missing the breakfast regularly, 123 (71.9%) had poor snacking behaviour. A significantly larger proportion of males had a higher frequency of snacking per day (69.3% versus 57.2%, p<0.0001) and consumed aerated drinks more frequently (22.6% versus 15.8%, p=0.011), skipped meals more often (58.6% versus 50.6%, p=0.022), and preferred adding fruits in snacks (78.1% versus 69.4%, p=0.005). Snacking frequency was proportionately higher among students of private colleges (73.6%) than that in the government colleges (55.1%). Participants from nonscience stream, nonvegetarians, and those with a tendency to skip the regular meals had significantly higher levels of poor snacking behaviour. Conclusions. The study population had a high level of poor snacking behaviour. Appropriate measures are needed among younger people to follow fixed eating patterns and avoid skipping of regular meals.